Hyperledger fabric blockchain-based medical document and prescription sharing system: Enhancing data security and traceability of the healthcare sector in Bangladesh - Abdullah, Mohammed Taher; Hasan, Ikramul; Iqbal, Shadab; Banik, Srijan; Dihan, Merazul Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.